Employing recent technologies for improved digital governance - Ponnusamy, Vasaki 1974-; Rafique, Khalid; Zaman, Noor 1972- (IGI Global, 2020)
"This book explores recent advances in the development, application, and impact of technologies in digital governance"--
Keywords: Public administration / Data processing; Municipal services / Data processing; Internet in public administration